What ever happened to Sabotage? ([New York?] : Black Cat Collective, 1990)
About Sabotage Anarchist Books, an anarchist bookstore at 96 Saint Marks Place, New York City.
[Signed]: "Dave Lawrence, Mary Shelley, Happy Mike, Jay Underhill (members of the Sabotage Collective at the time of its demise)"--page 11.
Keywords: Sabotage Anarchist Books (New York, N.Y.).; Sabotage Collective (New York, N.Y.).; Anarchists -- New York (State) -- New York; Bookstores -- New York (State) -- New York; Cooperative societies -- New York (State) -- New York